THE PREGNANT WOMEN BEHAVIOR IN USING PERSONAL PROTECTIVE EQUIPMENT DURING COVID-19 - Puspitasari, R.A. Helda; Nastiti, Ayu Dewi; Kusuma, Erik; Handayani, Dwining (Universitas Nahdlatul Ulama Surabaya, 2022)
Background: The COVID-19 outbreak has occurred worldwide and has resulted in fatalities. The death toll increases every day and continues to experience a significant increase. Until April 26, 2020, the cases increased rapidly to 8,882 in Indonesia and spread to 34 provinces with a mortality percentage of 8.365%. Symptoms that arise in every pregnant woman are very different depending on many things, one of which is the condition of obesity and the presence of comorbidities[1]. Obesity in pregnant women with COVID-19 can cause pulmonary embolism (pulmonary embolism). Obesity is closely related to a prothrombotic activity that triggers clotting in blood vessels, increasing the risk of pulmonary embolism. Objective: The purpose of the study was to determine the behavior of using personal protective equipment in pregnant women. Methods: The design used in this research is descriptive research. Descriptive research aims to describe important events that occur in the present. Descriptive research designs are divided into two types, namely survey research designs. A survey research design was used to collect information from a person's actions, knowledge, will, opinions, behavior, and values in this study. Results: The result showed that the description of anxiety based on age with the highest frequency is respondents aged 20-35 years, as many as 25 respondents (33.3%). The description of anxiety based on education with the highest frequency was among respondents with high school education, as many as 25 respondents (33.3%). Conclusion: This detailed data will be presented in the form of a table regarding the anxiety of pregnant women.